Effects of silver nanoparticles and various forms of silver on nitrogen removal by the denitrifier Pseudomonas stutzeri and their toxicity mechanisms - Fan, Zengzeng; Huang, Yahui; Duan, Ying; Tang, Zhu; Yang, Xinping (Ecotoxicology and environmental safety, 2024)
Silver nanoparticles (AgNPs) are widely used in daily life and industry because of their excellent antibacterial properties. AgNPs can exist in wastewater in various forms, such as Ag , Ag SO , Ag CO , Ag S, Ag O, and AgCl. To assess the potential environmental risk of AgNPs and various forms of Ag, their toxic effects were investigated using the common denitrifier species Pseudomonas stutzeri (P. stutzeri). The inhibitory effect of AgNPs and various forms of Ag on P. stutzeri growth and its denitrification performance occurred in a concentration-dependent manner. The denitrification efficiency of P. stutzeri decreased from 95%∼97% to 89∼95%, 74∼95%, and 56∼85% under low, medium, and high exposure doses, respectively, of AgNPs and various forms of Ag. The changes in cell membrane morphology and increases in lactate dehydrogenase (LDH) release indicated that AgNPs and various forms of Ag damaged the cell membrane of P. stutzeri. Oxidative stress caused by excessive accumulation of reactive oxygen species (ROS) increased superoxide dismutase (SOD) and catalase (CAT) activities and decreased glutathione (GSH) levels. Overall, this study will help elucidate the impact of AgNPs and their transformation products on nitrogen removal efficiency in wastewater biological treatment systems.